International Classification for Nursing Practice (ICNP®) - current state in the world and the stage of preparations for implementation in Poland - Kilańska, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2009)
The process of developing the International Classification for Nursing Practice (ICNP ® ) as a modern nursing classification of terminology, which has lasted for 20 years, allows one to observe the setting up of this tool, organization of use of this knowledge, as well as its adaptation to changing needs of users in various countries. In Poland many public health institutions do not have a fully working information system making it possible to identify nursing services and compare them with the same services offered by other institutions. The introduction of ICNP ® in a general health information system allows to unify nursing diagnosis language as well as reducing the time necessary for classical medical documentation, which makes available more time for direct patient care.